A Variation of the Mardešić Conjecture - Ishiu, Tetsuya (Topology Proceedings, 2024)
We shall show that if $d$ is a positive integer, $K_i$ is a compact linearly ordered topological space for each $i<d, Z_j$ is a nonseparable Hausdorff space for each $j<d$, and there is a continuous surjection from a countably compact subspace of $\prod_{i<d} K_i$ onto $\prod_{j<d} Z_j$, then every $Z_j$ is a continuous image of a countably compact GO-space. Several variations of this theorem are also proved.